A recombinant adenovirus targeting typical Aeromonas salmonicida induces an antibody-mediated adaptive immune response after immunization of rainbow trout. (August 2019) - Ling, Xiao-dong; Dong, Wei-tao; Zhang, Yong; Hu, Jun-jie; Liu, Ji-xing; Zhao, Xing-xu
Abstract: Aeromonas salmonicida, the oldest known fish pathogen and currently endemic throughout most of the world in both fresh and marine waters, causes severe economic losses to the salmon farming industry. Although there have been many studies on the prevention of furunculosis over the past few decades, it is still prevalent in many fisheries. In this study, a recombinant adenovirus vaccine candidate harboring the highly immunogenic Vapa gene (pAd-easy-cmv-Vapa) was successfully constructed and tested. The immune protection rate and specific antibody levels in the peripheral blood were then determined after immunizing rainbow trout. In addition, relative levels of IgM and IgT in the head kidney and hindgut before and after immunization were measured by quantitative reverse transcription PCR. Western blotting results indicated that the recombinant adenovirus could infect HEK-293 cells and express the A layer protein (encoded by Vapa ). Further, survival analysis of fish 28 days after challenge showed that immunization significantly lowered the mortality rate (40%) compared to that in the control group (76.6%) and empty vector group (73.6%). This also led to an increase in specific antibodies in peripheral serum. In addition, levels of IgM and IgT in the head kidney and hindgut were increased to varying degrees. In conclusion, our research provides a candidate vaccine for the prevention of Aeromonas salmonicida A450 infection in rainbow trout and lays the foundation for future research on adaptive immune mechanisms associated with rainbow trout antibodies. Highlights: Recombinant adenovirus vaccine candidate harboring Vapa gene successfully constructed. Adenovirus expresses A-layer protein (encoded by Vapa ) in HEK-293 cells. With vaccination, the survival of fish 28 days after challenge is improved. Levels of IgM and IgT in the head kidney and hindgut are increased with vaccination.